Effectiveness of routine provision of feedback from patient‐reported outcome measurements for cancer care improvement: a systematic review and meta-analysis - Sheng-Chieh Lu; I. Porter; J. M. Valderas; C. J. Harrison; Chris Sidey-Gibbons (SpringerOpen, 2023)
Abstract Background Research shows that feeding back patient-reported outcome information to clinicians and/or patients could be associated with improved care processes and patient outcomes. Quantitative syntheses of intervention effects on oncology patient outcomes are lacking. Objective To determine the effects of patient-reported outcome measure (PROM) feedback intervention on oncology patient outcomes. Data sources We identified relevant studies from 116 references included in our previous Cochrane review assessing the intervention for the general population. In May 2022, we conducted a systematic search in five bibliography databases using predefined keywords for additional studies published after the Cochrane review. Study selection We included randomized controlled trials evaluating the effects of PROM feedback intervention on processes and outcomes of care for oncology patients. Data extraction and synthesis We used the meta-analytic approach to synthesize across studies measuring the same outcomes. We estimated pooled effects of the intervention on outcomes using Cohen's d for continuous data and risk ratio (RR) with a 95% confidence interval for dichotomous data. We used a descriptive approach to summarize studies which reported insufficient data for a meta-analysis. Main outcome(s) and measures(s) Health-related quality of life (HRQL), symptoms, patient-healthcare provider communication, number of visits and hospitalizations, number of adverse events, and overall survival. Results We included 29 studies involving 7071 cancer participants. A small number of studies was available for each metanalysis (median = 3 studies, ranging from 2 to 9 studies) due to heterogeneity in the evaluation of the trials. We found that the intervention improved HRQL (Cohen's d = 0.23, 95% CI 0.11-0.34), mental functioning (Cohen's d = 0.14, 95% CI 0.02-0.26), patient-healthcare provider communication (Cohen's d = 0.41, 95% CI 0.20-0.62), and 1-year overall survival (OR = 0.64, 95% CI 0.48-0.86). The risk of bias across studies was considerable in the domains of allocation concealment, blinding, and intervention contamination. Conclusions and relevance Although we found evidence to support the intervention for highly relevant outcomes, our conclusions are tempered by the high risk of bias relating mainly to intervention design. PROM feedback for oncology patients may improve processes and outcomes for cancer patients but more high-quality evidence is required.